Comprehensive evaluation of transgenic rice lines expressing CSFV E2 protein in genetic stability, environmental safety and field adaptation - Chu, Hongyan; Zhang, Lei; Hao, Zhen; Hua, Yupeng; Hu, Wenjing; Liu, Ruijing; Lou, Yanyue; Gao, Wenming; Bian, Shuangli; Li, Fei; Han, Lichuang; Cheng, Wenbo; et al. (Frontiers in Plant Science, 2025)
Classical swine fever virus (CSFV) is a virulent pathogen that affects the global swine industry. Classical swine fever caused by CSFV is highly lethal and transmissible. Current attenuated vaccines present challenges, such as biosafety concerns and limitations in differential diagnosis. In previous study, we successfully constructed transgenic rice strains, E2-1 and E2-2, expressing the CSFV E2 antigen using a high-efficiency bioreactor system based on rice endosperm. This platform provides a safe and cost-effective approach for large-scale oral subunit vaccine production due to the protein-storage properties of rice endosperm and the absence of contamination risks from animal pathogens. In this study, systematic tracking of T1–T3 plant generations confirmed stable integration and continuous expression of the E2 gene, as verified by PCR and Western blot, with antigen titers in seeds remaining stable up to 2^7. Agronomic traits analysis revealed that the transgenic lines and the low-gluten rice variety showed significant improvements in plant height, grain number per spike, grain chalkiness, and other key indexes, thereby maintaining strong cultivation adaptability. Environmental safety tests demonstrated that the transgenic lines E2-2were more suitable for E2 vaccine production and posed no risk of genetic drift to surrounding weeds. This study is the first to report assessments of genetic stability, agronomic performance, and environmental safety of the CSFV E2 antigen expressed in multiple rice generations, which lays a key technical foundation for the commercial development of plant-derived swine fever vaccine.